(untitled) (American Journal of Pedagogical and Educational Research, 2024)
In this article, the novel “Imam Moturidi ” by the famous Uzbek writer Luqmon Boukhon is drawn into analysis. The article covers the tasks of elements of artistic composition in bringing an idea to the surface, the artistic-aesthetic functions of the means of speech, which carried out ideological communication in the text.